Some Remarks on the Problems of Art Research in Archaeology using the Example of Greek and Roman Sculpture - Bugaj, Ewa (Faculty of Archaeology, Adam Mickiewicz University in Poznań, 2021)
This article briefly presents some of the author’s research on art in archaeology, focusing especially on her contributions to research on Greek and Roman sculpture and its historiography. In particular, the problems of research on copies and imitations in Roman culture, Republican portraits of the elderly, the style of Greek sculpture, and the cult statue of Aphrodite of Cnidus are discussed.
Keywords: archaeology and art; Greek and Roman sculpture; Roman copies of Greek sculpture; Roman portraits; style of Greek sculpture